Study on coordinated voltage regulation strategy of flexible on-load tap changer and distributed generator - Jiaming Li; Qunhai Huo; Jingyuan Yin; Qiran Liu; Longfei Sun; Tongzhen Wei (Energy Reports, 2022)
The large number of distributed generations connected to the power grid brings the problems of reverse power flow and voltage rise. Due to the existence of “negative regulating voltage effect”, traditional on-load tap changer (OLTC) needs reactive power compensation device to make good voltage regulation. In this paper, the flexible OLTC with back-to-back voltage source converter (BTB-VSC) technology can generate a certain reactive power without a reactive power compensation device, which can achieve a better voltage regulation effect. Meanwhile, based on the principle of voltage sensitivity partition, we propose a coordinated voltage control strategy of flexible OLTC and distributed generators (DG), and coordinate the action of flexible OLTC and DG. The simulation model of the system operation is built in the Simulink software, and the research results show that a good voltage regulation effect can be achieved through the coordination of flexible OLTC and DG.